Pengaruh Model Discovery Learning Terhadap Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Kelas IV di Sekolah Dasar - Yetri Mai Yunita; Zuardi Zuardi (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research aims to know the influence model of Discovery Learning towards the learning outcome of students at an integrated thematic learning in class IV SDN 15 Ulu Gadut Subdistrict Pauh 2018/2019 lessons year of 97 people. The research sample class IVA totalling 24 people, class IVB which amounted to 24 people, the IVC classes totalling 25 persons and classes of IVD 24 people. The instruments used in this research is an objective test in the form of multiple choice. Technique of data analysis statistical test used was inferensial with t-test. The results showed that the mean value of experimental class that implements the layout of learning with a model of Discovery Learning was 79.37 is higher than the average of the control class that implements the conventional learning was 71.66. This proves that there are significant effects against the results of student learning on the integrated thematic learning in elementary school.